2017
DOI: 10.1039/c7fd00102a
|View full text |Cite
|
Sign up to set email alerts
|

Fast microwave-assisted acidolysis: a new biorefinery approach for the zero-waste utilisation of lignocellulosic biomass to produce high quality lignin and fermentable saccharides

Abstract: ReuseItems deposited in White Rose Research Online are protected by copyright, with all rights reserved unless indicated otherwise. They may be downloaded and/or printed for private study, or other acts as permitted by national copyright laws. The publisher or other rights holders may allow further reproduction and re-use of the full text version. This is indicated by the licence information on the White Rose Research Online record for the item. TakedownIf you consider content in White Rose Research Online to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Previous studies with M. pulcherrima reported that this yeast is capable of depolymerising long chain water-soluble oligosaccharides into short chain oligosaccharides; these latter being subsequently assimilated. 36 As described earlier, an increase in the S/W ratio decreases the amount of DP > 6 oligosaccharides in the liquids, producing a more accessible hydrolysate. Alternatively, alginic acid hydrolysates contained a particularly high level of inhibitors whereas there was negligible concentrations of inhibitors such as carboxylic acids and furans in the cellulose hydrolysates.…”
Section: Suitability For Fermentationmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies with M. pulcherrima reported that this yeast is capable of depolymerising long chain water-soluble oligosaccharides into short chain oligosaccharides; these latter being subsequently assimilated. 36 As described earlier, an increase in the S/W ratio decreases the amount of DP > 6 oligosaccharides in the liquids, producing a more accessible hydrolysate. Alternatively, alginic acid hydrolysates contained a particularly high level of inhibitors whereas there was negligible concentrations of inhibitors such as carboxylic acids and furans in the cellulose hydrolysates.…”
Section: Suitability For Fermentationmentioning
confidence: 79%
“…We recently reported that the yeast M. pulcherrima has excellent inhibitor tolerance and can metabolise a wide range of saccharide materials. 36 To assess the effect of the MW processing conditions on the fermentability of the hydrolysate from the three carbohydrates, M. pulcherrima was cultured in 24 well plates on the hydrolysate with additional N, P and microelements added. The yeast biomass growth is shown in Fig.…”
Section: Suitability For Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…One promising route to SCO is through oleaginous wine yeast Metschnikowia pulcherrima . The yeast can produce up to 40% oil content per cell through catabolism of a wide range of oligosaccharides and monosaccharides . Excitingly, the yeast can be cultured in nonsterile conditions due to a combination of culturing at low pH and production of antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a preference for glucose depolymerization was observed. Other authors have also found fruitful results when microwaves are implemented into hydrolysis processes (Zhou et al, 2017b, Zhou et al, 2017a, Li et al, 2018, Carnaroglio et al, 2015.…”
Section: Introductionmentioning
confidence: 98%